Radio IITA Star kid Balogun Adebayo - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Follow up on Children’s Day activities with engaging school visits designed to deepen pupils' understanding of IITA’s work and the importance of biodiversity.